Renal excretion of water in infants with acute gastroenteritis. Issue 249 (October 1971) - Patrick, John
Abstract : Infants with severe gastroenteritis were given water loads of 20 ml/kg body weight during their recovery. The renal responses were correlated with changes in body weight and osmolality. A water load was not excreted until the body weight had reached a peak. It is concluded that while volume depletion persists administration of hypotonic fluids leads to a fall in osmolality which will not be corrected by renal excretion of water. The relevance of this observation to the high incidence of neurological disturbances during the treatment of hyperosmolar states is discussed.